Foreign aid, investment and fiscal policy behavior: theory and empirical evidence - Simplice A. Asongu; Mohamed Jellal (African Governance and Development Institute (AGDI), 2014)
The paper provides theoretical and empirical justifications for the instrumentality of foreign aid in stimulating private investment and fixed capital formation through fiscal policy mechanisms. We propose an endogenous growth theory based on an extension of Barro (1990) by postulating that the positive effect of aid mitigates the burden of the taxation system on the private sector of recipient countries. The empirical validity is based on 53 African countries for the period 1996-2010. While the findings on the tax effort channel are overwhelmingly consistent with theory across specifications and fundamental characteristics, those of the government expenditure channel are a little heterogeneous but broadly in line with the theoretical postulations. Justification for the slight heterogeneity and policy implications are discussed.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa